Cyberbullying: The Silent Epidemic of The Digital Age - Noni Rihhadatul Aisya (Journal of World Science, 2024)
Cyberbullying is a very detrimental phenomenon that affects the mental health of adolescents and has become a major problem in the digital age. In recent years, cyberbullying cases have increased significantly, with victims not only limited to teenagers but also adults. This research aims to discuss cyberbullying, its impact on mental health, and the efforts that can be made to prevent and treat this problem. This study uses a mixed-methods approach to comprehensively understand the form, prevalence, and impact of cyberbullying. Quantitative data was collected through a survey targeting 2,000 participants from various regions. The results of the study show that cyberbullying is a form of harassment carried out through electronic media such as the Internet, mobile devices, and social media platforms. Unlike traditional bullying, which is limited by space and time, cyberbullying can happen anytime and anywhere, reaching a wider audience. Cyberbullying involves the use of digital technology to intentionally and repeatedly intimidate, humiliate, or harm another individual. Typical forms of cyberbullying include harassment, insults, dissemination of indecent photos or messages, personalization, exclusion, and cyber persecution. This research has implications that cyberbullying is a serious problem that requires immediate attention and action from all levels of society. Collaboration between educators, parents, policymakers, and tech companies is essential to address these issues and support victims.